Narrative Policy Framework (NPF) Analysis Terhadap Pelibatan Intelijen Negara dalam Penanganan Covid-19 di Indonesia - Bahtiar , Andhi; Munandar, Adis Imam (Jurnal Keamanan Nasional, 2020)
The policy of involving and taking steps by the State Intelligence Agency (BIN) as a secret agency in handling COVID-19 is deemed incompatible with its main duties and functions. The polemic arose when it was feared that this involvement could potentially lead to abuse of authority and the practice of reducing BIN to the role of other, more credible institutions in handling COVID-19. Through the analysis of the Narrative Policy Framework (NPF) on the existing literature review, this study will confront the policy counter-narrative with the dominant narrative used, namely that COVID-19 is a national security threat which is the responsibility of BIN as the first line of national defense. The metanarrative results in this study explain that the difference in perceptions between the two narratives originates from the trauma of intelligence practices in the past, which is faced with the dynamics of national security threats today and in the future.